2017
DOI: 10.1080/10872981.2017.1358579
|View full text |Cite
|
Sign up to set email alerts
|

The association of USMLE Step 1 and Step 2 CK scores with residency match specialty and location

Abstract: Background: For future physicians, residency programs offer necessary extended training in specific medical specialties. Medical schools benefit from an understanding of factors that lead their students to match into certain residency specialties. One such factor, often used during the residency application process, is scores on the USA Medical Licensing Exam (USMLE). Objectives: To determine the relationship between USMLE Step 1 and Step 2 Clinical Knowledge (CK) scores and students’ residency specialty match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 24 publications
(26 reference statements)
4
68
1
Order By: Relevance
“…In other words, learners with more honors grades and higher Step 1 scores had matched into higher ranked programs. This finding is consistent with the 2017 Gauer and Jackson study [9], which found that Step 1 scores are significantly associated with specialty match.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, learners with more honors grades and higher Step 1 scores had matched into higher ranked programs. This finding is consistent with the 2017 Gauer and Jackson study [9], which found that Step 1 scores are significantly associated with specialty match.…”
Section: Discussionsupporting
confidence: 91%
“…The emphasis placed on this examination score for the selection of a residency is understood from the beginning of medical school. This is especially true for those students desiring to match into their first-choice of residency or highly competitive specialties (Gauer and Jackson, 2017;Mitsouras, et al, 2019). A recent study demonstrated (Mitsouras, et al, 2019) that a difference in COMLEX and USMLE scores was more pronounced for those students matching into highly competitive specialties rather than into first choice, with a larger difference in mean scores between students matching into specialties of high versus low competitiveness, than between students matching into their first versus non first choice residency (Mitsouras, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Step 3 is taken during the first year of residency and evaluates the application of medical knowledge to the supervised practice of medicine. Of these, Step 1 scores have been shown to play an important role in residency selection by standardizing academic achievements of students from different schools, in predicting success in clinical clerkships and Step 2 examinations, and in board examinations taken during residencies [3][4][5][6][7][8][9]. Therefore, parameters influencing student performance on Step 1 examinations such as the Medical College Admission Test (MCAT) and related preparatory materials are of interest to both students as well as medical schools.…”
Section: Introductionmentioning
confidence: 99%